7a+6a=-14+8a+7a

Simple and best practice solution for 7a+6a=-14+8a+7a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7a+6a=-14+8a+7a equation:



7a+6a=-14+8a+7a
We move all terms to the left:
7a+6a-(-14+8a+7a)=0
We add all the numbers together, and all the variables
7a+6a-(15a-14)=0
We add all the numbers together, and all the variables
13a-(15a-14)=0
We get rid of parentheses
13a-15a+14=0
We add all the numbers together, and all the variables
-2a+14=0
We move all terms containing a to the left, all other terms to the right
-2a=-14
a=-14/-2
a=+7

See similar equations:

| (2x+29)=180 | | 11x+1=-1+1+x | | 2.5=6.5-0.8x | | 3y-5(2y+1)=-4-5(-1-y) | | 34=2x+5(5+4) | | -4.9(5.4n=1.6)=32,15+0.2n | | 2(p−6)=4(2p−3) | | D=9/7(m-27) | | 5=-2(u+5)+-3 | | -3(t-3)-16=-4(t+2) | | 60=-5(-4x-8) | | (3x-10)+(x+183)=(x-7) | | 6(x+4)=-2x+72 | | 2=7+p/2 | | (3x-33)+(2x+29)=180 | | 24p+12-18=10+2p-6 | | 47=-8a-9 | | -2x+(-7)x+18=17+9 | | 9.6-2x.4x=-3 | | 5=3(j-5)-1 | | x-0.20x=496.40 | | 8y+1=y+36 | | x-4=-41 | | x-0.20=496.40 | | x2-6=8 | | 7=-v+2 | | 9x-(2x-5)=12 | | -145=5(-9+n) | | (2+x)(4-2x+x2)=0 | | 8x-10=4x-10 | | x/3+7=x/2-5 | | 7.5+k7.5+k−7.5k​ =10=10−7.5=2.5​ |

Equations solver categories